2015
DOI: 10.1038/ncomms7725
|View full text |Cite
|
Sign up to set email alerts
|

RhoA and ROCK mediate histamine-induced vascular leakage and anaphylactic shock

Abstract: Histamine-induced vascular leakage is an integral component of many highly prevalent human diseases, including allergies, asthma, and anaphylaxis. Yet, how histamine induces the disruption of the endothelial barrier is not well defined. By using genetically modified animal models, pharmacologic inhibitors, and a synthetic biology approach, here we show that the small GTPase RhoA mediates histamine-induced vascular leakage. Histamine causes the rapid formation of focal adherens junctions, disrupting the endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
167
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(175 citation statements)
references
References 57 publications
6
167
2
Order By: Relevance
“…Therefore it has been speculated that the formation of prostate carcinoma may be associated with overexpression of RhoA (30,31). The present study observed that prostate cells expressed ROCK/PTEN protein, and the expression of ROCK/PTEN protein in prostate carcinoma is also higher than that in BPH.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Therefore it has been speculated that the formation of prostate carcinoma may be associated with overexpression of RhoA (30,31). The present study observed that prostate cells expressed ROCK/PTEN protein, and the expression of ROCK/PTEN protein in prostate carcinoma is also higher than that in BPH.…”
Section: Discussionsupporting
confidence: 56%
“…Prostate carcinoma cells may express RhoA protein, and the expression of RhoA protein in prostate carcinoma is higher than that in benign prostatic hyperplasia (BPH) (30). Therefore it has been speculated that the formation of prostate carcinoma may be associated with overexpression of RhoA (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…53 This has been shown to be essential for permeability induced by thrombin, VEGF, histamine and TNF-a. [54][55][56] In contrast, RhoA activation in response to angiopoietin-1 has been described to result in cell-cell junction stabilization. This endothelial barrier-protective effect of RhoA in response to angiopoietin-1 is mediated via the Rho-effector mDia, inducing actin polymerization.…”
Section: Endothelial Adherens Junction Control By Rho Gtpasesmentioning
confidence: 98%
“…55,56 Also, both SHP2 and Ga signaling can result in RhoA activation. 57,58 How then can these events occur specifically at one Tyr residue of the same protein with an almost opposite outcome? Although more detailed research should be performed to fully clarify this point, but we speculate that the signals require more proteins within one complex that can act in a very local and transient manner.…”
Section: Paracellular and Transcellular Migrationmentioning
confidence: 99%